Microstructural visual pathway abnormalities in patients with primary glaucoma: 3 T diffusion kurtosis imaging study. Issue 6 (June 2018) - Xu, Z.F.; Sun, J.S.; Zhang, X.H.; Feng, Y.Y.; Pan, A.Z.; Gao, M.Y.; Zhao, H.
Abstract : Aim: To evaluate microstructural visual pathway damage in patients with primary glaucoma (PG) by using 3 T diffusion kurtosis imaging (DKI). Materials and methods: The study was approved by the ethics committee, and all participants provided written informed consent. Ten patients with PG were examined. Twenty healthy individuals served as control subjects. DKI was performed with a GE Silent 3 T magnetic resonance imaging (MRI) unit. Mean diffusivity (MD), fractional anisotropy (FA), and mean kurtosis (MK) maps were automatically created. Mean MK, MD, and FA values were calculated for each part of the visual pathway. Results: No abnormalities in the shape and signal intensity were observed along the entire visual pathway in patients and the control group on the conventional MRI. Higher MD, and lower MK and FA were observed in the optic nerves (ON), lateral geniculate nucleus (LGN), optic radiations (OR), and visual cortex (VCx) of PG patients, as compared with control subjects. A significantly higher MD was observed in the ON ( p< 0.01), and significantly lower FA was observed in OR ( p< 0.05). Additionally, significantly lower MK was observed in the ON, LGN, and VCx, except for OR ( p< 0.01). Changes of DKI parameters in the ON were the most distinct. Conclusion: Glaucoma is a complex neurological disease that affects the entire visual pathway. MK derived from DKI would be a better biomarkers than FA and MD in detecting microstructural damage. Highlights: Our results comfirmed that primary glaucoma (PG) is a multifactorial, progressive and neurodegenerative optic disease. Diffusional kurtosis imaging (DKI) characterizes non-Gaussian water diffusion was first to study in damage of visual pathway in glaucoma patients. Our results showed that significantly decreased MK in the whole visual pathway. Compared with FA and MD, MK seemed to be more sensitive to reveal abnormality.